Siedem gór, siedem strumieni. Wiersze o sensie istnienia - Citko, Katarzyna (Strategie komunikacyjne i procesy twórcze, 2022)
Mountains and streams are inherently connected with the mountain landscape, constituting its most beautiful scenes. Captivating beauty provokes artists; mountains with their streams and sources are a frequent theme in art, also in poetry. After all, poets do not only praise the beauty of rock landscapes, but look for a deeper meaning in them, reaching the roots of human existence and reflection on its essence. One of the persistently recurring poetic themes that have been inspired by images of a mountain and a stream is a hike. It evokes the symbolic image of a man traversing his life like a wanderer climbing to the top. The mountains here become an imaginative image of the journey of the human spirit, created and called to ascend from earth to the heights of heaven. It is an upward journey, an ascent towards the sphere of the sacred; there is, however, the opposite direction, downwards, with the stream flowing through its waters: towards the lowlands, towards the hell's gates, towards the mouth of the end of the river's existence, melting in the swaying waves of abyssal depths. The article analyzes seven selected poems exploring symbolic images of mountains and streams. These are works by Joanna Ślósarska, Kazimierz Przerwa-Tetmajer, Zbigniew Herbert, Adam Zagajewski, Czesław Miłosz, John Paul II and Katarzyna Citko. They are connected by reflection on the purpose and sense of human existence, contained in symbolic images of mountains and streams.